Severe hemophilia A caused by an unbalanced chromosomal rearrangement identified using nanopore sequencing. (20th May 2019) - Chatron, Nicolas; Schluth‐Bolard, Caroline; Frétigny, Mathilde; Labalme, Audrey; Vilchez, Gaëlle; Castet, Sabine‐Marie; Négrier, Claude; Sanlaville, Damien; Vinciguerra, Christine; Jourdy, Yohann
Abstract: Essentials No F8 genetic abnormality is detected in about 2% of severe hemophilia A patients. Detection of F8 structural variants remains a challenge. We identified a new F8 rearrangement in a severe hemophilia A patient using nanopore sequencing. We highlight the value of single‐molecule long‐read sequencing technologies in a genomics laboratory. Background: No F8 genetic abnormality is detected in about 2% of severe hemophilia A patients using conventional genetic approaches. In these patients, deep intronic variation or F8 disrupting genomic rearrangement could be causal. Objective: To characterize, in a genetically unresolved severe hemophilia A patient, a new Xq28 rearrangement disrupting F8 using comprehensive molecular techniques including nanopore sequencing. Results: Long‐range polymerase chain reaction (PCR) performed throughout F8 identified a nonamplifiable region in intron 25 indicating the presence of a genomic rearrangement. F8 messanger ribonucleic acid (mRNA) analysis including 3′rapid amplification of complementary deoxyribonucleic acid (cDNA) ends and nanopore sequencing found the presence of a F8 fusion transcript in which F8 exon 26 was replaced by a 742‐bp pseudoexon corresponding to a noncoding region located at the beginning of the long arm of chromosome X (Xq12; chrX: 66 310 352‐66 311 093, GRCh37/hg19). Cytogenetic microarray analysis found the presence of a Xq11.1q12 gain of 3.8 Mb. The PCR amplification of junction fragments and fluorescent in situ hybridization (FISH) analysis found that the Xq11q12 duplicated region was inserted in the F8 intron 25 genomic region. Conclusion: We characterized a novel genomic rearrangement in which a 3.8‐Mb Xq11.1q12 gain inserted in the F8 intron 25 led to an aberrant fusion transcript in a patient with severe hemophilia A (HA), using comprehensive molecular techniques. This study highlights the value of single‐molecule long‐read sequencing technologies for molecular diagnosis of HA especially when conventional genetic approaches have failed.